Inovasi Teknologi Pengelolaan Tanah dan Air untuk Meningkatkan Produktivitas Lahan - Purnama Mendrofa, Ayu Indah (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
Technological innovation in soil and water management plays a crucial role in sustainably increasing agricultural land productivity. This article aims to review the latest technological innovations applied in soil and water management, such as soil testing, balanced fertilization, amelioration, precision agriculture, as well as Internet of Things (IoT)-based irrigation systems and digital water management. The method used is a literature review of various freely accessible national and international journals. The review shows that the implementation of these technological innovations can improve the efficiency of agricultural input use, optimize crop yields, and reduce negative environmental impacts. The integration of digital technology also accelerates data-driven decision-making, supporting agriculture that is adaptive to climate change. Therefore, technological innovation in soil and water management is essential to support future food security and land productivity.